Role of the carbohydrate recognition domains of mouse galectin-4 in oligosaccharide binding and epitope recognition and expression of galectin-4 and galectin-6 in mouse cells and tissues - Marková, Vladimíra; Smetana, Karel; Jeníková, Gabriela; Láchová, Jitka; Krejciríková, Veronika; Poplstein, Martin; Fábry, Milan; Brynda, Jirí; Alvarez, Richard; Cummings, Richard; Maly, Petr (International journal of molecular medicine, 2006)
Galectin-4 and its homologue galectin-6 are members of the tandem-repeat subfamily of monomer divalent galectins. Expression of mouse galectin-4 and galectin-6 by RT-PCR using primers designed to distinguish both galectin transcripts indicates that both are expressed in the small intestine, colon, liver, kidney, spleen and heart and P19X1 cells while only galectin-4 is expressed in BW-5147 and 3T3 cell lines. In situ hybridization confirmed the presence of galectin-4/-6 transcripts in the liver and small intestine. Galectin-4 is expressed in spermatozoons and oocytes and its expression during early mouse emryogenesis appears in 8-cell embryos and remains in later stages, as tested by RT-PCR. To study the role of carbohydrate recognition domains (CRDs) in oligosaccharide binding and epitope recognition, we cloned mouse full-length galectin-4 and galectin-6 cDNA and constructed bacterial expression vectors producing histidin-tagged recombinant galectin-4 and its truncated CRD1 and CRD2 forms. Oligosaccharide binding profile for all recombinant forms was assessed using Glycan Array available through the Consortium for Functional Glycomics. Acquired data indicate that mGalectin-4 binds to α-GalNAc and α-Gal A and B type structures with or without fucose. While the CRD2 domain has a high specificity and affinity for A type-2 α-GalNAc structures, the CRD1 domain has a broader specificity in correlation to the total binding profile. These data suggest that CRD2 might be the dominant binding domain of mouse galectin-4. Mapping of epitopes reactive for biotinylated his-tagged CRD1, CRD2 and mGalectin-4 performed on mouse cryosections showed that all three forms bind to alveolar macrophages, macrophages of red pulp of the spleen and proximal tubuli of the kidney and this binding was inhibited by 5 mM lactose. Interestingly, mGalectin-4, but not CRD forms, binds to the suprabasal layer of squamous epithelium of the tongue, suggesting that the link region also plays an important role in ligand recognition.